Unintentional transport of fungal propagules to the Antarctic biome – growth opportunities at low temperatures - Augustyniuk-Kram, Anna (Studia Ecologiae et Bioethicae, 2016)
Microfungi relatively easily disperse and colonize a variety of substrates, withstanding various, often extreme environments. Therefore, they spread all over the world. The aim of this study was to determine whether propagules of fungi accidentally transported to biome of Antarctica were able to grow at low temperatures. In the studies were used seven isolates of fungi: Penicillium sp., Aspergillus flavus, Alternaria alternata, Cladosporium cladosporioides, Trichoderma viride, Geotrichum candidum and Botrytis cinerea. The isolates came from dust samples collected from tourists and members of scientific expeditions (their clothes, shoes and equipment) arriving at the station H. Arctowski on King George Island in the South Shetland archipelago. Fungal growth was measured at 0, 5, 10, 22°C (as a control) and 10°C, but after having frozen inoculum at -15°C for a period of 7 days. All tested species of fungi did not grow at the temperature of 0°C. A. flavus was the only one not grow at a temperature of 5°C. A. flavus and G. candidum haven’t also grown after a temporary freeze of inoculum. Fungi, which did not grow at a temperature of 0°C after moving to higher temperatures resumed their growth. Of the two species that did not grow after freezing, i.e. G. candidum and A. flavus, only the first resumed its growth at 22°C. Sporulation of the studied fungi in most cases was most abundant at 22°C. Some species (G. candidum, T. viride and B. cinerea) did not produce spores at lower temperatures.